PAK4 regulates stemness and progression in endocrine resistant ER-positive metastatic breast cancer. (28th August 2019) - Santiago-Gómez, Angélica; Kedward, Thomas; Simões, Bruno M.; Dragoni, Ilaria; NicAmhlaoibh, Roisin; Trivier, Elisabeth; Sabin, Verity; Gee, Julia M.; Sims, Andrew H.; Howell, Sacha J.; Clarke, Robert B.
Abstract: Despite the effectiveness of endocrine therapies to treat estrogen receptor-positive (ER+) breast tumours, two thirds of patients will eventually relapse due to de novo or acquired resistance to these agents. Cancer Stem-like Cells (CSCs), a rare cell population within the tumour, accumulate after anti-estrogen treatments and are likely to contribute to their failure. Here we studied the role of p21-activated kinase 4 (PAK4) as a promising target to overcome endocrine resistance and disease progression in ER + breast cancers. PAK4 predicts for resistance to tamoxifen and poor prognosis in 2 independent cohorts of ER + tumours. We observed that PAK4 strongly correlates with CSC activity in metastatic patient-derived samples irrespective of breast cancer subtype. However, PAK4-driven mammosphere-forming CSC activity increases alongside progression only in ER + metastatic samples. PAK4 activity increases in ER + models of acquired resistance to endocrine therapies. Targeting PAK4 with either CRT PAKi, a small molecule inhibitor of PAK4, or with specific siRNAs abrogates CSC activity/self-renewal in clinical samples and endocrine-resistant cells. Together, our findings establish that PAK4 regulates stemness during disease progression and that its inhibition reverses endocrine resistance in ER + breast cancers. Highlights: PAK4 predicts for failure of endocrine therapies and poor prognosis. PAK4 drives stemness and progression in ER + metastatic breast cancer. Targeting PAK4 abrogates breast CSC activity and restores sensitivity to endocrine treatments. Targeting PAK4 will improve outcome of ER + breast cancer patients.